IN SILICO MOLECULAR TARGETING AND ADMET PROFILING OF BETA-SITOSTEROL AS A MULTI-TARGET THERAPEUTIC CANDIDATE - Fendy Prasetyawan; Yuneka Saristiana; Lisa Savitri (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Beta-sitosterol is a naturally occurring phytosterol with potential biological activities, including anticancer effects. This study aimed to evaluate the pharmacokinetic characteristics and molecular targets of beta-sitosterol using in silico approaches involving ADMET analysis and target prediction. The ADMET results indicated that beta-sitosterol exhibited favorable membrane permeability and high absorption potential; however, it demonstrated poor aqueous solubility and high plasma protein binding, which may affect its bioavailability. Additionally, metabolic prediction suggested potential involvement of cytochrome P450 enzymes in beta-sitosterol biotransformation. Target prediction analysis revealed that beta-sitosterol may interact with multiple proteins involved in lipid metabolism and hormonal regulation. The highest predicted affinity was observed toward NPC1L1, a protein involved in cholesterol absorption, as well as nuclear receptors including LXR-α, ROR-γ, and androgen receptor, which regulate lipid metabolism and hormone signaling. Furthermore, beta-sitosterol was predicted to interact with HMG-CoA reductase and several cytochrome P450 isoforms involved in cholesterol biosynthesis and steroidogenesis. The findings suggest that beta-sitosterol possesses a multi-target profile associated with lipid metabolism and hormonal regulation pathways.